2014
DOI: 10.1111/jopr.12213
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coating of Gypsum‐Based Molds for Maxillofacial Prosthetic Silicone Elastomeric Material: The Surface Topography

Abstract: Silicone elastomers with lower surface roughness of maxillofacial prostheses can be obtained simply by coating a gypsum mold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…The mean surface roughness (Ra) of the modified silicone elastomers molded in coated gypsum materials was 0.12 ± 0.08 μm, lower than unmodified silicone elastomers molded in non‐coated gypsum materials (0.67 ± 0.22 μm). This result was dependent on the surface at which the materials were placed, and one of these modifications was intended to decrease surface roughness . This in vitro study was performed to investigate whether surface topography modifications of silicone elastomers could decrease the adherence of C. albicans , S. mutans , and S. aureus to external maxillo‐facial prostheses or obturators made of silicone elastomers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean surface roughness (Ra) of the modified silicone elastomers molded in coated gypsum materials was 0.12 ± 0.08 μm, lower than unmodified silicone elastomers molded in non‐coated gypsum materials (0.67 ± 0.22 μm). This result was dependent on the surface at which the materials were placed, and one of these modifications was intended to decrease surface roughness . This in vitro study was performed to investigate whether surface topography modifications of silicone elastomers could decrease the adherence of C. albicans , S. mutans , and S. aureus to external maxillo‐facial prostheses or obturators made of silicone elastomers.…”
Section: Discussionmentioning
confidence: 99%
“…Silicone elastomer material was packed in the molds. This technique has been previously described in the first part of this series of investigations …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the specimens (eight per group) were tested for surface roughness before aging by AFM (JPK BioAFM; Bruker Optics, Berlin, Germany), which provides images with near-atomic resolution for measuring surface topography and can also quantify surface roughness down to the angstrom-scale [22]. The other half of the samples were subjected to artificial aging in an aging chamber (QUV Accelerated Weathering Tester; Q-Lab, Cleveland, OH, USA) according to American Society for Testing and Materials (ASTM) G154 cycle 1 (approximate wavelength: 340 nm; energy irradiance: 0.89 W m −2 nm −1 ; the exposure cycle included 8 h of UV irradiation at 60 °C ± 3 °C black panel temperature and 4 h of condensation at 50 °C ± 3 °C black panel temperature) [33] for 750 h. Afterward, the aged samples were removed and examined for surface roughness using AFM.…”
Section: Experimental Design and Sample Preparationmentioning
confidence: 99%
“…Similarly, Goiato et al [21] reported a decline in surface roughness following 60 days of storage in a chemical disinfection solution. Another study demonstrated a decrease in roughness for maxillofacial silicone elastomers processed against coated gypsum materials, with AFM analysis indicating noticeable variations in surface roughness [22]. Alwan et al [23] observed a proportional increase in the surface smoothness of maxillofacial silicone with the increase in the duration of artificial aging.…”
Section: Introductionmentioning
confidence: 99%